Optimizing PCB-based resonators for inductive power transfer - Song, Yingying (Nanyang Technological University, 2025)
This dissertation introduces an innovative method for improving the design and performance of printed circuit board (PCB)-based resonators for inductive power transfer (IPT) systems. The study investigates advanced resonator configurations and circuit strategies to enhance the reliability and efficiency of wireless energy transfer. A quasi-sine inverter utilizing zero-voltage switching (ZVS) is devel oped to minimize switching losses, while self-resonant PCB coils are exam ined to improve the system’s quality factor (Q). To optimize design parameters, Latin Hypercube Sampling (LHS) is employed, offering efficient exploration of the multidimensional parameter space. The simulation models are built using ANSYS Electronics and validated through experimental measurements, focusing on key performance indicators such as self-resonant frequency and transfer effi ciency. Experimental prototypes are fabricated to verify the theoretical findings, demonstrating a notable improvement in overall IPT system efficiency. This work contributes a systematic framework for the design and optimization of high-frequency resonators, providing valuable insights into practical imple mentation. The results demonstrate substantial improvements in energy transfer performance, positioning PCB-based resonators as a promising solution in wire less power systems. Future directions include expanding the optimization frame work to account for dynamic misalignment and higher power levels.